Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3346/jkms.2021.36.e325
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 Affected Healthcare Workers in the Hospital Locked Down due to Early COVID-19 Cases in Korea

Abstract: Background The healthcare workers (HCWs) were exposed to never-experienced psychological distress during the early stage of the coronavirus disease 2019 (COVID-19) pandemic. The aim of this study was to investigate how the COVID-19 pandemic affected the mental health of HCWs during the hospital lockdown period due to mass healthcare-associated infection during the early spread of COVID-19. Methods A real-time online survey was conducted between April 14–18, 2020 among H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…These authors found a path analysis model clearly showing that the predictors of depression in healthcare workers during the early stage of the COVID-19 pandemic are work-related stress and generalized anxiety. Moreover, burnout, considered a condition characterized by feelings of energy depletion or exhaustion, increased mental distance from one’s job, and reduced professional efficacy can be included in the path between stress and depression [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These authors found a path analysis model clearly showing that the predictors of depression in healthcare workers during the early stage of the COVID-19 pandemic are work-related stress and generalized anxiety. Moreover, burnout, considered a condition characterized by feelings of energy depletion or exhaustion, increased mental distance from one’s job, and reduced professional efficacy can be included in the path between stress and depression [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous complications, from minor to even fatal ones, have been repetitively reported in the media 13 14 and literatures 3 11 12 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 although complications required further medical evaluation were rarely happened ranging from 0.0012% 24 to 0.026%. 20 In addition, excessive quarantine burden and stressful condition of the COVID-19 pandemic 37 38 occasionally causes uncomfortable testing by the examiner who may not fully understand the nasopharyngeal anatomy or clinically cautious events related to nasopharyngeal swabs. 11 39 In this study, a literature review of adverse events related to nasopharyngeal COVID-19 testing was performed to raise attention about rare but existing risks.…”
Section: Introductionmentioning
confidence: 99%
“…also reported HCWs isolated as a cohort in the locked downed hospital in South Korea experienced higher depression and anxiety. ( H.A. Lee et al., 2021 ) A large cross-sectional survey which investigated mental health impact of the first wave of COVID-19 pandemic on Spanish HCWs reported that having quarantined or isolated are risk factors for mental disorders.…”
Section: Introductionmentioning
confidence: 99%